Pengaruh Terapi Touch And Talk Terhadap Kecemasan Pre Operatif Pada Anak Usia Sekolah di RSUD Kabupaten Bintan - Evi Junita Manurung; Wulan Pramadhani; Indah Purnama Sari (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
The anxiety felt by children will have an impact on stress in children. Some children are unable to express their anxiety openly and quiet children usually do not have good coping skills in dealing with anxiety. Many methods have been used to approach children with the aim of reducing hospitalization, starting with play therapy, music, reading stories, drawing. Touch and talk therapy is carried out by providing touch and motivation to children. Where children feel more comfortable when touched. This study aims to find out the effect of touch and talk therapy on preoperative anxiety in school-aged children at the Bintan District Hospital. This research design is a quasi-experimental one group pretest-posttest design. The sample in this study was 30 school-aged children treated in the Gardenia Room at the Bintan District Hospital and the data were analyzed using the Wilcoxon range test. The results show that there is a significant influence between the average anxiety level score during the pre-test and post-test (mean pre-test = 60.17 to mean post-test = 26.07) with p value = 0.000 (p value <0.05). This therapy can be used as an alternative for pre-operative intervention in children at the hospital.